(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The painting of Mithila is more than sculpture. A collective of women communicate their desires, visions, goals, wishes and ambitions to the population through this artistic art. If you ask them what they are doing, We are writing this khobar or gnawer, they will answer. For them, their art form is a sort of script in which they interact with the male folk or the inhabitants of the rest of the country. (Hamralokani kohbara yaa gahavara likhait chee). In the process of drawing, they are the artistic artist who paints their emotions. They are builders and, in perfection, are similar to Heaven. Mithila painting is mostly women-centered, though some men have even jumped into this creativity because of wealth, but it is women’s creativity and empowerment in its essence and purpose, even today. Painting is a product of human history and life and a portrayal thereof. Mithila Cohber painting is one of the folk arts that portrays the image of the community of mithila and the concept of empowerment for women. A art like this is drawn mainly by women. The real problem of the mithila community is the organic content used in art. During weeding, the Cohber painting portrays not only the sexual arouse, awareness and dilemma but also the motif of deity, goddess, mythological and religious values that lead the powerful society tool for women to express their dilemma of feeling in the outside world. This research paper explores the status of women and art as a important medium for women’s liberation. It reflects on how the gender problem has been tackled by Cohber painting and empowers women in this work by painting.